Development of hybrid controller of wheeled robot for mine detection - Rashid, Muhammad Mahbubur; Hussain, M.A; Khan, Md. Raisuddin (2009)
In this work, design a hybrid control wheeled robot which is capable of detecting buried landmines and marking their localization in uneasy accessible areas, while enabling the operator to control the robot wirelessly from a distance. As a universal solution to the landmine problem is unlikely to be achieved in the short time, according to what many other researchers think, time is worth spent on trying to solve a specific aspect of the global problem, rather than treating the problem as a whole. The problem becomes even more difficult if the environment is hazardous, presents a potentially wide temperature range, and is subject to rain, dust and other natural factors. Such environments are typical for minefields. Landmines still continue to kill, injure and penalize on a daily basis mainly a civilian population. Replacing human demines or trained dogs in the mine searching task is challenging, and promises better detection capabilities. This paper presents an autonomous mine searching wheeled robot using hybrid controller.